Free Trade Zones in Oman: A Descriptive Analysis - Hossain, Mohammad Zakir (IJRDO - Journal of Applied Management Science, 2015)
The aim of this paper is to present a descriptive analysis about the free trade zones in Oman. Oman has established its Free Trade Zones (FTZ) at the beginning of 2000 in order to diversify its non-oil revenues and investments into its national economy. In fact, the FTZ of a country provides opportunities to the investors a free access to industrial infrastructure along with the option of 100 per cent return of their revenues. It also creates boosting international trade relations and Foreign Direct Investments (FDI) of the country.